Persepsi Guru terhadap Materi Mitigasi Perubahan Iklim yang Diaplikasikan melalui Pengintegrasian Visi II Literasi Sains dan Pendekatan STEM - Nursofa, Risma; Hamdu, Ghulam; Elan, Elan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Climate change mitigation is a crucial subject that needs to be well understood. However, many elementary school students still lack adequate climate change mitigation skills. This study aims to explore teachers’ perceptions of climate change mitigation education for children by integrating the STEM approach and Vision II of Scientific Literacy. The background of this research is Indonesia's commitment to the Paris Agreement to combat climate change, despite the fact that the country remains one of the largest contributors to greenhouse gas emissions. Therefore, climate change mitigation education needs to be taught contextually through STEM and scientific literacy approaches. This research employed a qualitative method with data triangulation through questionnaires, semi-structured interviews, and document analysis. Thematic analysis was conducted using Braun & Clarke’s (2006) model. The findings indicate that teachers perceive terms such as greenhouse effect, greenhouse gases, and global warming as difficult for students to understand, thus hindering meaningful comprehension of climate change mitigation. Furthermore, there is a lack of instructional media that simplifies these concepts for easier student understanding. Learning materials, student worksheets (LKPD), and media that connect climate change mitigation to socio-scientific issues rooted in environmental and social contexts are also currently unavailable.Mitigasi perubahan iklim merupakan materi yang penting untuk dipahami. Namun masih banyak siswa sekolah dasar yang memiliki kemampuan mitigasi perubahan iklim. Penelitian ini bertujuan untuk mengetahui persepsi guru terhadap pembelajaran mitigasi perubahan iklim pada anak dengan mengintegrasikan pendekatan STEM dan Visi II Literasi Sains. Latar belakang penelitian ini adalah komitmen Indonesia dalam Perjanjian Paris untuk mengatasi perubahan iklim, meskipun nyatanya Indonesia masih menjadi salah satu penyumbang emisi gas rumah kaca terbesar. Oleh karena itu, pembelajaran mitigasi perubahan iklim perlu diajarkan secara kontekstual melalui pendekatan STEM dan literasi sains. Metode penelitian menggunakan pendekatan kualitatif dengan triangulasi data melalui angket, wawancara semi-terstruktur, dan studi dokumentasi. Data dianalisis secara tematik berdasarkan model Braun & Clarke (2006). Hasil penelitian menunjukkan bahwa guru menganggap istilah-istilah seperti efek rumah kaca, gas rumah kaca, dan pemanasan global sulit dipahami siswa, sehingga menghambat pemahaman bermakna tentang mitigasi perubahan iklim. Selain itu, belum ada media pembelajaran yang menyederhanakan konsep tersebut agar mudah dipahami siswa. Pembelajaran, LKPD, dan media yang mengaitkan mitigasi perubahan iklim dengan isu sosiosaintifik berbasis lingkungan dan sosial juga belum tersedia.